Scouting in the construction of youth citizenships: conceptions of politics of young scouts - Rodrigues, Mariana (2019)
The scientific production presents gaps concerning the exploration of the potential contributions of scouting in the construction of the subjectivities and citizenship experiences of the young people involved in the movement. Questioning their “place” in the everyday experiences of young scouts and based on a qualitative approach, this study seeks to deepen the knowledge about the conceptions of politics of 359 young scout members of the Portuguese Catholic Scout Association, aged between 15 and 22 years; it also explores the conditions under which these young scouts learn what it means to be a citizen in a democratic political context. The results reveal that these young people present different conceptions of politics with different levels of complexity and focus, varying between deep disinterest and indifference and a conception of politics as an action in the different spheres of society. However, most participants conceive politics as an action confined to the government apparatus, which supports social organization.   Keywords: Scouting. Young people’s discourses. Conceptions of politics.